A Cross-sectional Study on Medicolegal Post-mortem Examination Conducted in a Tertiary care Medical College of West Bengal - Bandyopadhyay, S; PS , Harsha; Mahata, S; Das , A; Adhya , S (Journal of Indian Academy of Forensic Medicine, 2024)
Unnatural and suspicious deaths are grounds for performing medicolegal autopsy examinations. It is performed by forensic medicine  experts and doctors trained in autopsy to determine the cause of death which is the prime objective of medicolegal autopsy. Apart from that,  manner and mode of death, time since death, identification of the deceased are other important objectives. Mortality data from various  unnatural deaths gives important information regarding the different violent incidents prevailing in society. The following study aims to  make a cross-sectional observation on various unnatural deaths in a medical college police morgue in a particular time of the year. The  police inquest reports and the autopsy reports were reviewed before starting the post-mortem examinations in the police morgue. It was a  prospective study done over two months for the study time in the initial months of covid lockdown. All the cases during that period were  included in the study. Data were tabulated first, then subjected to appropriate statistical methods and published as results. Of the 103 cases  a male predominance of 69 cases was observed, and majority (90.2%) were Hindu by religion. The majority of the deceased were of age  range 21 to 30 years followed by 41 to 50 years. Poisoning (35.3%) and hanging (33.3%) were found to be the most common causes of  death whereas natural disease caused death in 6.9% of cases. The suicidal rate was the highest (81.1%) Suicidal death continues to be the  majority of unnatural deaths. Poisoning and hanging claimed most of the lives whereas road traffic accidents, and accidental falls, caused  significant mortality.
Keywords: Autopsy; Postmortem examination; Medicolegal; Unnatural death; Tertiary care; West Bengal